Gambaran Profil dan Infeksi Cacing Usus pada Pekerja di Tiga Rumah Potong Hewan Provinsi Riau - Esy Maryanti; Yola Zenia; Afrinaldi Aldi; Fadly Mulia; Mislindawati Linda (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: Intestinal worm infestation is still a health problem in Indonesia that is often neglected. This disease is chronic in nature and is strongly influenced by factors of environmental hygiene and sanitation. Slaughterhouses are places where animals in the form of cows, goat/ sheep and pigs are slaughtered to be distributed to meat sellers or to reataurants. This study aims to determine the profil description and incidence of intestinal worm infestations in workers in three slaughterhouses in Riau Province.Methods: This study was a cross-sectional descriptive study in August – October 2020 in three slaughterhouses in Riau Province ( Pekanbaru, Duri and Dumai city). Stool examination was carried out using the Kato Katz Method at the Parasitology Laboratory Medical Faculty, Universitas Riau. Result: Do A total 37 workers who were examined found 35 men, age range 21 – 30 yo as much as 38% with latest education 46% was high school, length of work 1 – 5 years as much as 57% and as much as 41% have normal nutriotional status. Six workers found positive for intestinal worm infections (16%), there were three hookworm infections and one each to Trichuris trichiura, Oxyuris vermicularis and Hymenolepis diminuta.Conclusion : There were still intestinal worm infections among workers in the three slaughterhouses. Intestinal worm infection usually occurs in children and rarely occurs in adults and if it occurs in adults this may be due to poor hygiene and sanitation of the slaughterhouse workers.